Normalized Difference Vegetation Index (NDVI) applied to the agricultural indigenous territory of Kashaama, Venezuela (UNED Research Journal, 2019)
Introduction: multi-temporal analysis of satellite images help monitor the evolution of plant communities and agricultural crops, especially in vulnerable areas. Objective: to analyze the behavior of the Normalized Difference Vegetation Index (NDVI) in the indigenous agricultural community of Kashaama, Venezuela, during the period 2012-2013. Methods: the data used was MOD13Q1 of the MODIS sensor, which contains the NDVI. Result: the average behavior of the NDVI is directly associated with the main physiographic and climatic characteristics of the region. Conclusion: the method facilitated the elaboration of maps that, together with computerized treatment of the satellite images, reliably discriminate vegetation types and their states, e.g. cultivated versus natural savannah.
Keywords: remote sensing; vegetation; climate; sustainability; land.